COMMUNICATING ENGLISH IN SPECIALISED DOMAINS a festschrift for maurizio. (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This volume is dedicated to Maurizio Gotti, in honour of his long and noteworthy academic career. Having served as Full Professor of History of the English Language and of English Language and Translation for more than two decades at the University of Bergamo, Italy, Gotti made significant contributions to multiple areas of study including specialized discourses, lexicography, history of the English language and language teaching. This wide-ranging collection brings together essays from these fields of enquiry authored by scholars whose academic input have interacted in various ways with ideas.